ANTIMICROBIAL ACTIVITY AND PHYTOCHEMICAL PROPERTIES OF ACTINODAPHNE GLOMERATA LEAVES EXTRACT - Ine, Suharyani; Kuspradini, Harlinda; Manalu, Julinda (Asian Journal of Pharmaceutical Research and Development, 2019)
This study aimed to determine the antimicrobial activity and chemical compounds by phytochemical analysis of Actinodaphne glomerata leaves. The extraction was performed by maceration method using n-hexane solvent. The antimicrobial activity was tested by agar diffusion method against Candida albicans, Staphylococcus aureus, Streptococcus mutans and Streptococcus sobrinus. The n-hexane crude extracts was tested for its antimicrobial activity using 125, 250 and 500 μg/well of concentrations. Based on phytochemical analysis, it showed that n-hexane extract of A. glomerata leaves contained alkaloids, triterpenoid and carbohydrates. The extract inhibited all tested microorganisms and the best inhibition zone was shown against S. sobrinus (19.56 mm) at concentration 500 μg/well.